Development of an ergonomic musculoskeletal model to estimate muscle forces during vertical jumping - Nishida, I.; Maeda, M.; Gordon, D.; Robertson, E.; Shirase, K. (Procedia Engineering, 2011)
This study investigated a musculoskeletal model that includes the function of the antagonistic muscles and biarticular muscles and models muscles acting across the hip, knee and ankle joints, simultaneously. Furthermore, this study can be applied to dynamic motions. One vertical jump trials were conducted to validate the proposed model. Electromyograms (EMGs) of tibials anterior, gastrocnemius, soleus, rectus femoris, vastus lateralis, semimembranosus, biceps femoris, short head and gluteus maximus were used to compare with the estimated muscle forces. The results showed that the muscle forces estimated by the proposed method had a stronger correlation with EMGs than those of an optimization method. The correlations of the proposed method and the optimization method were 0.4 and 0.01 of TA, 0.95 and 0.86 of GAS, 0.95 and 0.93 of SOL, 0.94 and 0.01 of RF, 0.93 and 0.97 of VAS, 0.83 and 0.91 of SM, 0.75 and 0.01 of BFSH and 0.95 and 0.92 of GMAX. Thus, the proposed method was considered to successfully estimate the muscle forces during vertical jumping.